Does feeling collective responsibility for intergroup harm lead to infrahumanization? - Robert A. Brennan; Florence E. Enock; Carl J. Bunce; Harriet Over (PLoS ONE, 2025)
Previous research has suggested that subtle dehumanization can occur as a consequence of harming others. According to this research, participants who feel a sense of collective responsibility for their ingroup contributing to the harm experienced by an outgroup may perceive members of that group as experiencing uniquely human emotions to a lesser extent, compared to when they do not feel responsible. We sought to understand whether these results replicate in two novel intergroup contexts: understanding UK residents’ perceptions of those who disproportionately experience the harmful effects of climate change in Nigeria, and employees working in exploitative conditions in fast fashion supply chains. Across three well-powered and pre-registered studies, we successfully manipulated perceived harm against the target groups and perceived ingroup responsibility for that harm. However, we found no evidence for the previously reported relationship between one’s sense of collective responsibility for harm and the perceived extent that target outgroup members experience uniquely human emotions. Instead, a more straightforward pattern was found in all three studies, whereby participants perceived outgroup members to experience negative emotions to a greater extent when harm towards them has been made salient. This trend was irrespective of whether the emotions were uniquely human (e.g., admiration, shame) or shared with other animals (e.g., joy, sadness). The often evoked relationship between the need to justify harm and the tendency to subtly dehumanize harmed outgroup members may be less common than is often assumed.